Breathing patterns during sleep in patients with nocturnal asthma. Issue 8 (August 1987) - Morgan, A D; Rhind, G B; Connaughton, J J; Catterall, J R; Shapiro, C M; Douglas, N J
Abstract : Breathing patterns early and late in the night, at the same sleep stage, were compared in six healthy subjects and 15 adults with nocturnal asthma, to try to identify changes of overnight bronchoconstriction, and breathing patterns at different sleep stages, to see whether there were changes related to sleep stages that were indicative of bronchoconstriction. Despite an average 31% fall in FEV1 overnight in the patients with asthma, neither breathing frequency nor expiratory time, which might be expected to change during bronchoconstriction, was different early in the night from late in the night, nor did they differ between sleep stages. There was no evidence of asynchronous movement of the chest and abdomen in any patient. This study did not identify any abnormality of breathing pattern that would indicate the development of nocturnal asthma without the need to awaken the patient.